2015
DOI: 10.1016/j.jiph.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Information-Motivation and Behavioral Skills (IMB) model in risky sexual behaviors amongst male students

Abstract: As AIDS is not merely a hygienic problem but a disease that creates a great deal of economic, cultural, and social problems, it is necessary for most of the state and nongovernmental organizations and individuals to participate in both controlling AIDS and preventing it. As no effective vaccine or therapy for this disease exists currently, the only method for avoiding being afflicted by this disease is prevention. The present study aims to examine the Information-Motivation and Behavioral Skills (IMB) model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Moreover, research done by Bahrami and Zarani (2015) showed the perception about the risk of HIV and AIDS infection significantly related to the sexual behavior. The perception about the risk became the consideration to modify the sexual behavior (from risky sexual behavior to the positive behavior) [19]. Sex education in the school could lower the intention of risky sexual behavior of adolescence [20].…”
Section: Results and Analysismentioning
confidence: 99%
“…Moreover, research done by Bahrami and Zarani (2015) showed the perception about the risk of HIV and AIDS infection significantly related to the sexual behavior. The perception about the risk became the consideration to modify the sexual behavior (from risky sexual behavior to the positive behavior) [19]. Sex education in the school could lower the intention of risky sexual behavior of adolescence [20].…”
Section: Results and Analysismentioning
confidence: 99%
“…Increasing the information skills possessed by PLWHA in addition to improving behavioral skills in treatment, also can improve behavior in taking precautions related to the risk of opportunistic infections (Bahrami & Zarani, 2015). Information skills possessed by PLWHA in the form of drug adherence, dietary adherence and physical activity compliance are very influential and have a significant relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, knowledge promotion leads to better adaptation in stressful situations. Another study 9 reported that lack of motivation and nonfavorable attitudes toward HIV-infected individuals was resulted from lack of knowledge; so, motivation is considered as a prerequisite for collecting information. However, the mere promotion of information does not change the healthy behavior and interventions are needed to provide information and promote motivation.…”
Section: Discussionmentioning
confidence: 99%
“…The IMB is used in ART adherence, self-care behaviors in diabetics (nutrition and exercise), 7 predicted condom use, 8 and high-risk sexual behaviors among young people. 9 According to this model, information is a “prerequisite for performing health behavior and real knowledge about drugs.” 10 Motivation consists of two factors: personal motives, which include beliefs as well as beliefs and attitudes, and social motives, which include perceived social support for engagement in a particular behavior. 11 Perceived susceptibility or individual perception of risk is a prerequisite for the motivation to change risky behaviors.…”
Section: Introductionmentioning
confidence: 99%